A study of student satisfaction in a blended learning system environment / Hashim Saidin - Saidin, Hashim (2014)
Study in blended learning environment becomes a challenge to the students who are also teachers. To be a successful student, the student should be equipped with learning strategies such as blended learning. A quantitative research using questionnaires as an instrument for data collection process was conducted. The participants were 4th semester students. They were using blended learning in their studies. A total of 106 respondents answered the questionnaires. The questionnaires contain the surveyed elements on student perception of learning satisfaction, monitoring skills, independent learning and time management. The findings showed that students' level of perceptions on monitoring, learning satisfaction, independent learning and time management skills in a blended learning methods is high and indicates that they were comfortable with the learning process they have gone through. The correlational analyses identified a strong relationship between learning satisfaction and monitoring skills (r = 0.708, p-value < 0.05), between learning satisfaction and independent learning(r = 0.707, p-value < 0.05) and between learning satisfaction and time management (r = 0.745, p-value < 0.05). The regression analysis shows there is a relationship between the dependent variable (learning satisfaction) and the independent variables (monitoring skills, and time management). However, independent variables namely independence learning is not a significant contributor to dependent variable (learning satisfaction). Further investigations and transformation plan should be conducted in order to examine the student's success rates using blended learning method.